2010
DOI: 10.1111/j.1468-2397.2009.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in youth problem behavior in Sweden: a pragmatic cost analysis of MST from a randomized trial with conduct disordered youth

Abstract: Olsson TM. Intervening in youth problem behavior in Sweden: a pragmatic cost analysis of MST from a randomized trial with conduct disordered youth Int J Soc Welfare 2010: 19: 194–205 © 2009 The Author(s), Journal compilation © 2009 Blackwell Publishing Ltd and the International Journal of Social Welfare. Within the context of a randomized trial, this study assessed the costs of treating conduct disorder with multisystemic therapy (MST) or treatment as usual (TAU) for 156 youth in Sweden. From the perspective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…As such, it is a source which is unable to capture cost variation between patients. In addition, the average unit cost for the interventions provided is characterized by high variation [25]. Even so, this study found that both the top-down and bottom-up approaches were reliable, indicating that for purposes of economic evaluation both approaches may be useful when difference in cost is of concern as opposed to absolute cost.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As such, it is a source which is unable to capture cost variation between patients. In addition, the average unit cost for the interventions provided is characterized by high variation [25]. Even so, this study found that both the top-down and bottom-up approaches were reliable, indicating that for purposes of economic evaluation both approaches may be useful when difference in cost is of concern as opposed to absolute cost.…”
Section: Discussionmentioning
confidence: 69%
“…When a unit cost could not be estimated through one of the aforementioned methods, a unit cost was estimated by taking the average of the available unit costs as calculated by one of the aforementioned methods (n = 151). The average was calculated by intervention type [24,25] and (calendar) year. For example, the average unit cost for all counseling services during 2006 or the average unit cost for aggression replacement training (ART) during 2004.…”
Section: Bottom-up Costingmentioning
confidence: 99%
“…For example, there are several methodological options available for the estimation of unit price (ibid., for empirical example see, Olsson 2010a). An investigator may, through sensitivity analysis, choose to adjust the unit price estimate in order to assess how method or other factors may have impacted the results of the economic evaluation (e.g., Olsson 2009Olsson , 2010b. Similarly, an investigator may choose to incorporate other studies' clinical results or make changes to organizational variables to test how changes in effectiveness or organizational efficiency might impact an intervention's economic result.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Lastly, services that integrate multiple systems can be costly. Although such services have been supported by evidence (Letourneau et al, 2009), the inclusion of multiple individuals, treatment protocols, and provider training can lead to a greater expense (Harpell & Andrews, 2006;Olsson, 2010), limiting accessibility for many with economic disparities. Despite these and other service challenges, professionals are increasingly valuing systemic and family-oriented models of service delivery.…”
Section: Donna Ruchmentioning
confidence: 99%